An exploratory study on the influence of orange juice on gut microbiota using a dynamic colonic model. (June 2016) - Duque, Ana Luiza Rocha Faria; Monteiro, Magali; Adorno, Maria Angela Tallarico; Sakamoto, Isabel Kimiko; Sivieri, Katia
Abstract: The aim of this research was to evaluate the influence of fresh orange juice (FOJ) and pasteurized orange juice (POJ) on gut microbiota using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) in a long-term experiment. SHIME® vessels were used to investigate orange juice fermentation throughout the colon and to assess changes in microbial composition and fermentation metabolites (short-chain fatty acids, or — SCFA, and ammonium). Antioxidant activity of the SHIME® vessels and juice was also evaluated. The FOJ increased (p ≤ 0.05) Lactobacillus spp., Enterococcus spp., Bifidobacterium spp., and Clostridium spp. and reduced (p ≤ 0.05) enterobacteria. The POJ increased (p ≤ 0.05) Lactobacillus spp. and reduced (p ≤ 0.05) enterobacteria. The PCR-DGGE analysis showed a reduction in total bacteria population richness values. The FOJ and POJ increased (p ≤ 0.05) butyric, acetic, and propionic acid concentrations, whereas ammonium production was reduced. High values of antioxidant activity were observed as a result of the FOJ and POJ treatments. Principal component analysis indicated that both POJ and FOJ juices had a positive influence on gut microbiota. The FOJ and POJ were found to exhibit selective prebiotic activity, particularly in terms of gut microbiota. This finding is in agreement with increases in both SCFAs and commensal bacteria, as well as with decreases in ammonium levels, though total bacteria richness values were reduced. Graphical abstract: Highlights: Fresh orange juice (FOJ) and pasteurized orange juice (POJ) may have a prebiotic effect on gut microbiota in the SHIME®. FOJ and POJ significantly increased commensal bacteria in SHIME® vessels. FOJ and POJ significantly increased SCFA concentration in SHIME® vessels. FOJ and POJ significantly reduced ammonium concentration in all SHIME® vessels. FOJ and POJ increased antioxidant activity in all SHIME® vessels.